Quorum quenching bacillus sonorensis isolated from soya sauce fermentation brine. - Yin, Wai Fong; Tung, Hun Jiat; Sam, Choon Kook; Koh, Chong Lek; Chan, Kok Gan (2012)
An N-acylhomoserine lactone (AHL)-degrading bacterial strain, L62, was isolated from a sample of fermentation brine of Chinese soya sauce by using rich medium agar supplemented with soya sauce (10% v/v). L62, a rod-shaped Gram positive bacterium with amylolytic activity, was phylogentically related to Bacillus sonorensis by 16S ribosomal DNA and rpoB sequence analyses. B. sonorensis L62 efficiently degraded N-3-oxohexanoyl homoserine lactone and N-octanoylhomoserine lactone. However, the aiiA homologue, encoding an autoinducer inactivation enzyme catalyzing the degradation of AHLs, was not detected in L62, suggesting the presence of a different AHL-degrading gene in L62. To the best of our knowledge, this is the first report of AHL-degrading B. sonorensis from soya sauce liquid state fermentation.